Birth order and parental and sibling involvement in sex education. A nationally-representative analysis. Issue 2 (4th March 2019) - Elton, Lotte; Palmer, Melissa; Macdowall, Wendy
ABSTRACT: This analysis set out to identify associations between birth order and sexual health outcomes, focusing on family involvement in sex education and early sexual experiences. The third National Survey of Sexual Attitudes and Lifestyles is a stratified probability sample survey of 15 162 men and women aged 16–74 in Britain. Logistic regression was conducted to identify odds ratios for the association between birth order and sexual health outcomes. Multiple logistic regression was performed adjusting for socio-demographic factors and sibling number. Middle-born and last-born men had lower odds of reporting ease talking to parents about sex around age 14 and learning about sex from their mothers. Last-born women had lower odds of reporting a parental main source of sex education or having learned about sex from their mother. Findings represent an exploratory analysis in an under-researched area, and provide the basis for further research on the association between birth order and parental involvement in sex education, as well as the role and impact of sex education provided by older siblings.